Description of Macutula, a new genus of jumping spiders from Northeastern Brazil (Araneae: Salticidae: Amycoida) - Ruiz, Gustavo Rodrigo Sanches (Zootaxa, 2011)
Three new species from Northeastern Brazil are described and included in the newly proposed genus Macutula gen. nov. The type species M. aracoiaba sp. nov. and M. caruaru sp. nov. are described based on specimens from the State of Pernambuco, while M. santana sp. nov. is based on specimens from the State of Bahia.